Przeciw emigracji? Proza Tadeusza Nowakowskiego - Szadkowska, Ewelina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
This article presents a picture of emigration, contained in novels and short stories of Tadeusz Nowakowski. Polish emigrants are passive and divided; they wait for a change - fall of communism in Polish People’s Republic. They live “in the past” , in the circle of remembrances and dream about independence Poland. Nowakowski shows faults of Poles in exile, but he troubles about their future.